PENINGKATAN KOMPETENSI GURU DALAM MENERAPKAN PEMBELAJARAN DARING MASA PANDEMI COVID-19 DI SDN IMPRES KINANDAL KECAMATAN LIANG KABUPATEN BANGGAI KEPULAUAN: SDN IMPRES KINANDAL KECAMATAN LIANG KABUPATEN BANGGAI KEPULAUAN - YOSES KALANDING (Mitra Pendidikan, 2022)
This study aims to improve the ability of teachers to apply online learning during the Covid 19 pandemic at SDN Impres Kinandal. The type of research used by the author in this research is school action research. According to Arikunto (Suyadi, 2012), PTS is a combination of meanings from the words "research, action and school". The method used in this PTS is to use the method developed by Riel (2007) which divides the action research process from each cycle into stages. -stages: (1) planning; (2) implementation of actions; (3) data collection and analysis or in other methods known as the observation stage; and (4) reflection This school action research was carried out at SDN Imppres Kinandal, Liang District, Banggai Islands Regency for three months, from September to November 2021. In this study, the subject of the research was the teacher of SDN Impres Kinandal, Liang District, Banggai Islands Regency in the odd semester of the 2021 academic year 2022 This research was carried out for 2 cycles (Arikunto, 2006) namely Cycle I and II. In Cycle I, online learning activities were carried out and in the second cycle, online learning activities were carried out from the results of improvements in cycle I. Analysis of the data used by researchers using comparative descriptive analysis, namely by comparing the implementation of online learning The teacher's understanding in online learning that was carried out during the learning process at SDN Impres Kinandal in Cycle I was 1,260. The average value is 37, with a percentage of 77.20%. Thus the understanding of the teachers at SDN Impres Kinandal is in the Good Enough category. Then it increased after the implementation of Cycle II of Online Learning which was carried out during the learning process at SDN Impres Kinandal, the total was 1,339. The average value is 39, with a percentage of 82.04%. Thus the understanding of the teachers at SDN Imppres Kinandal is in the Good category. The results showed that the teacher's understanding of online learning at SDN Impres Kinandal was in the good category